Environmental Postcolonialism in Faulkner’s Go Down, Moses and Fatris MF’s Merobek Sumatra - Eva Najma; Agustin, Suciati; Syofyan, Donny; Zulprianto, Zulprianto (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Andalas, 2024)
This article discusses environmental postcolonialism practices and the impacts on the environment and indigenous people in William Faulkner's Go Down, Moses and Fatris MF's Merobek Sumatra. Go Down, Moses describes the story of land grabbing from the Chickasaw and Choctaw communities and land conversion into cotton plantations in the Southern United States. On the other hand, Fatris MF's Merobek Sumatra captures the expropriation of the customs territory of Anak Dalam communities and land conversion to oil palm plantations in Sumatra. The writers apply the postcolonial ecocriticism approach by Huggan and Tiffin. The data is analyzed through the qualitative method and the result is presented using the descriptive method. The result of the analysis found that there are three practices of environmental postcolonialism in Go Down, Moses and Merobek Sumatra, which are: (1) Dualistic thinking on environment; (2) Land grabbing from indigenous communities, and (3) Nature exploitation. It is also found that these practices have negative impacts on nature and the indigenous people as represented in both books.